2018
DOI: 10.31629/ph.v2i1.330
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Literasi Digital Mahasiswa Calon Guru Biologi Melalui Proyek Video Amatir Berbasis Potensi Lokal Pada Mata Kuliah Ekologi Tumbuhan

Abstract: The purpose of this study to know the degree of digital literacy of the students teacher towards video project based on local potency in West Borneo. This study uses descriptive qualitative methods. The subjects of the study was taken by using systematic sampling technic. The technic of collecting data uses the indirect communication, observation, and direct communication. Collecting data uses observation sheet, and dialogue sheet. The technic of data analysis uses descriptive statistical analysis. The result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Whatever this place should be owned by every individual besides getting knowledge from the school. Digital Literacy Kahar (2018:2) argues that "digital literacy is the ability to use digital technology to understand, evaluate, use, and create information." In line with Nurnannah's opinion, dkk (2017) argued that literacy was the capacity to understand and use information in various formats that came from various digital sources displayed through computers.…”
Section: Self Directed Learningmentioning
confidence: 99%
“…Whatever this place should be owned by every individual besides getting knowledge from the school. Digital Literacy Kahar (2018:2) argues that "digital literacy is the ability to use digital technology to understand, evaluate, use, and create information." In line with Nurnannah's opinion, dkk (2017) argued that literacy was the capacity to understand and use information in various formats that came from various digital sources displayed through computers.…”
Section: Self Directed Learningmentioning
confidence: 99%
“…The low score or value of UPBJJ Pekanbaru and Pangkal Pinang students on B4 for writing essays about the AEC issues becomes the thing that should be worried abo ut. It is a line of research conducted by (Kahar, 2018), the level of digital literacy of students is very low on the component of looking for local potential information and sharing information. This is likely based on the inability to use technology and the internet (Sukor et al, 2010) that the economy influences social status, i.e.…”
Section: T Able 1 Digital Literacy Of Upbjj Pekanbaru Dan Pangkal Pinang Studentsmentioning
confidence: 99%
“…Several studies that analyzed student digital literacy, including those conducted by Kahar (2018), examined the Digital Literacy Analysis of Prospective Biology Teacher Students through Amateur Video Projects. The results of his research showed that the digital literacy level of prospective teacher students was classified as at a medium level, while the indicator of using technology in distinguish whether the source is valid or not, the student's ability level is in the low category.…”
Section: Introductionmentioning
confidence: 99%